2021
DOI: 10.1186/s12904-021-00735-0
|View full text |Cite
|
Sign up to set email alerts
|

Opioid therapy vs. multimodal analgesia in head and neck Cancer (OPTIMAL-HN): study protocol for a randomized clinical trial

Abstract: Background Radiation-induced mucositis (RIM) pain confers substantial morbidity for head and neck cancer (HNC) patients undergoing radiotherapy alone (RT) or chemoradiotherapy (CRT), often reducing treatment compliance. However, no standard currently exists for the treatment of RIM, and high dose opioid therapy, with its associated side effects and increased risk for chronic opioid use, remains the cornerstone of HNC pain management. The goal of this randomized clinical trial is to compare mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…After some studies have been undergone, it seems that multimodal analgesic therapy may become the now gold standard in the treatment of pain caused by radiotherapy-induced mucositis. This implies the association between NSAIDs + acetaminophen + pregabalin +/-opioid [26].…”
Section: Discussionmentioning
confidence: 96%
“…After some studies have been undergone, it seems that multimodal analgesic therapy may become the now gold standard in the treatment of pain caused by radiotherapy-induced mucositis. This implies the association between NSAIDs + acetaminophen + pregabalin +/-opioid [26].…”
Section: Discussionmentioning
confidence: 96%
“…Pain reporting mechanisms are subjective and often lack standardization; this is especially true in the management of HNC, in which pain is a significant part of symptom burden and opioid use is a mainstay for pain management. 13,27,28 Given that these patients are vulnerable to the stressors associated with both the disease and its management, it is especially important to examine prevalent characteristics in the group of patients with HNC who report pain, as well as pain management for these patients. We found that while there was no significant difference between the number of pain incidents reported by White patients with HNC and non-White patients with HNC, White patients were significantly more likely to receive new pain medications; reported time to pain resolution was also longer for White patients than for non-White patients.…”
Section: Discussionmentioning
confidence: 99%